Inguinal ureter herniation evaluated with magnetic resonance imaging: a case report - Matteo Renzulli; Guido Marzocchi; Giulio Vara; Beniamino Corcioni; Anna Maria Ierardi; Caterina Gaudiano; Rita Golfieri (Journal of Medical Case Reports, 2020)
Abstract Background The herniation of the ureter into the inguinal canal is a rare condition, but probably underreported. Acquired nephroptosis could cause herniation of the ureter and, therefore, when diagnosed, a full study of the urinary tract should be performed especially in patients with inguinal hernia. Case presentation We present the case of an 86-year-old white man with a herniated ureter likely caused by acquired nephroptosis presenting with acute urinary retention, documented with magnetic resonance imaging for the first time. Conclusions The Fast Imaging Employing Steady State Acquisition sequence on magnetic resonance imaging, for many reasons, could allow correct evaluation of the urinary tract, especially in cases of renal dysfunction that contraindicate the use of intravenous contrast agents.